Effect of analgesic drugs on tooth sensitivity induced by in-office dental bleaching: A systematic review and meta-analysis - Costa, Rayanna Thayse Florêncio; Moraes, Sandra Lúcia Dantas; Lemos, Cleidiel Aparecido Araujo [UNESP]; Souto-Maior, Juliana Raposo; Do E Vasconcelos, Belmiro Cavalcanti; Pellizzer, Eduardo Piza [UNESP] (Operative Dentistry, 2020)
Objective: This systematic review evaluates the effect of preemptive analgesia on tooth sensitivity induced by in-office tooth bleaching. Methods: The review was structured based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) checklist. The methods were recorded at PROSPERO (CRD42018095440). Randomized clinical trials, studies published in English, and studies in which the efficacy of preemptive analgesia with analgesic and anti-inflammatory medications prior to in-office tooth bleaching was compared with that of placebo were included. PubMed/MEDLINE, Scopus, Web of Science, and Cochrane Library were used for searching. The electronic search provided 373 articles, and seven of them were selected based on the inclusion criteria. Results: Immediately after time point, a significant reduction of dental sensitivity was observed in the drug group compared to the control group (p=0.02; mean difference [MD]: -0.90; confidence interval [CI]: -1.63 to -0.16), while there was no significant difference at up to one-hour (p=0.22; MD: -0.42; CI: -1.09 to -0.25), at 1-24-hour (p=0.88; MD: -0.05; CI: -0.61 to 0.72), or 24-48-hour (p=0.69; MD: 0.05; CI: -0.21 to 0.32) time points. The incidence of sensitivity during the procedure was not statistically different between the groups (p=0.64; MD: 0.91; CI: 0.92 to 1.15). The nonsteroidal anti-inflammatory drug group showed a statistically significant reduction (p=0.04; MD:-0.69; CI: -1.36 to -0.03) in tooth sensitivity compared with the other groups. Conclusions: This systematic review and metaanalysis demonstrated that the medications analyzed did not interfere with the incidence of sensitivity symptoms. Regarding the intensity, no difference was observed between the drug and placebo groups at the up to one-hour, 1-24-hour, or 24-48-hour time points, and there was a statistically significant difference at the zero-hour time point in favor of the drug group. However, based on the variables that influenced this result, it should be considered with prudence because a small difference was observed.